Estudio Etnobotánico de Plantas Útiles empleadas en la Comunidad Shuar Kukush – Granja Chicaña del cantón Yantzaza de la provincia de Zamora Chinchipe - Berrú Chamba, María de los Ángeles (2015)
This ethnobotanical study conducted in the Shuar community Kukush -Farm Chicaña Yantzaza canton in the province of Zamora Chinchipe, were conducted semi-structured and implemented 29 community informants interviews. A total of 41 species were identified, of which 11 are arboreal, 8 shrubs, herbaceous 20 and 2 epiphytes. The most representative families, with three species each, are Urticaceae, Solanaceae Malvaceae, Asteraceae and Araceae. Also the species with the highest number of applications are Ageratum conyzoides L. (4), Ruta graveolens L. (3), Celtis iguanacea (Jacq). Sarg. (3) and Begonia fischeri Schrank (3). 25 applications are known in total, among the most common include (12 spp) for food, (6 spp) to the horror, (4 spp) diarrhea (4 spp) cold, respectively, and the lowest use are to (1 spp) stomach pain (1 spp) inflammations. Finally six forms of preparation and the three main cooking (21 spp), crushed (18 spp) and directly (7 spp) were determined. Less employed forms: Ointment (4 spp), syrup (4spp) and infusion (3spp).